1983
DOI: 10.1017/s0021859600033529
|View full text |Cite
|
Sign up to set email alerts
|

Effects of eight factors on the growth and nutrient uptake of winter wheat and on the incidence of pests and diseases

Abstract: A multifactorial experiment sown to winter wheat cv. Hustler in autumn 1978 tested the effects of combinations of the following eight factors, each at two levels: drill type, sowing date, amount of nitrogen, division of nitrogen, irrigation, autumn pesticide (aldicarb), summer aphicide (pirimicarb), and fungicide (carbendazim, maneb and tridemorph).The mean grain yield of all plots was 9-7 t/ha and the best eight-plot treatment mean was 11-3 t/ha. The factors that had the greatest effect on yield were aphicide… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
49
3
3

Year Published

1985
1985
2005
2005

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 56 publications
(60 citation statements)
references
References 21 publications
5
49
3
3
Order By: Relevance
“…In common with other studies comparing Napplication rates in winter wheat (Prew et al, 1983;Leitch & Jenkins, 1995), we found least disease on the crops receiving least N. Previous reports have suggested that this is because low-N crops become senescent more rapidly, so that green leaf area (GLA) becomes limiting on disease progress. However, our study suggested that S. tritici was responsible for most of the senescence recorded in both high-and low-N treatments.…”
Section: Effect Of Crop Husbandry On Disease Progresssupporting
confidence: 89%
“…In common with other studies comparing Napplication rates in winter wheat (Prew et al, 1983;Leitch & Jenkins, 1995), we found least disease on the crops receiving least N. Previous reports have suggested that this is because low-N crops become senescent more rapidly, so that green leaf area (GLA) becomes limiting on disease progress. However, our study suggested that S. tritici was responsible for most of the senescence recorded in both high-and low-N treatments.…”
Section: Effect Of Crop Husbandry On Disease Progresssupporting
confidence: 89%
“…The parasitoid did not attempt to oviposit in aphids killed by the fungus. KEY-WORDS : Cereal aphids, parasitoid behaviour, Aphidiidae, Entomophthorales, fungus-parasitoid interactions.The rose grain aphid, Metopolophium dirhodum (Walker), is an occasional pest of cereals in Great Britain and Europe, responsible in some years, most recently 1979, for large yield losses (Prew et al, 1983). The numbers of this aphid are normally controlled by a complex of natural enemies including hymenopterous parasitoids and fungi of the order Entomophthorales.…”
mentioning
confidence: 99%
“…Two possible explanations have been put forward by McNeill & Southwood (1978), and Prew et al. (1983).…”
Section: Discussionmentioning
confidence: 97%